Pursuing Sustainable Development Goals: The Performance of Türkiẏe in the Centennial of the Republic - Billur Engin Balin; Hatice Dilara Mumcu Akan; Ferda Karagoz Ozenc; Ozcan Garan (Istanbul University Press, 2024)
As the centennial commemoration of the establishment of the Republic of Türkiye draws near, it is opportune to reflect upon the advancements achieved thus far and the challenges that persist in our endeavour to construct a sustainable and prosperous nation. This editorial book represents a collective effort to examine, assess, and comprehend Türkiye's advancements in relation to the Sustainable Development Goals (SDGs) during a significant juncture coinciding with the nation's centennial commemoration. It encompasses a wide range of disciplines, such as economics, sociology, history, education, international relations, political science, tourism, environment, and the natural sciences, among various others. In doing so, it adopts an interdisciplinary approach to address the complex societal aspects of sustainable development. The 2030 Agenda for Sustainable Development, endorsed by all United Nations (UN) member states in 2015, has 17 Sustainable Development Goals (SDGs) at its core. This agenda serves as a compelling appeal for both developed and developing nations to collaborate in a global partnership. The underlying concept posits that sustainable development necessitates the harmonious integration of economic, social, and environmental dimensions. Türkiye, a nation characterised by a rich historical background and diverse cultural heritage, has diligently strived to achieve these worldwide objectives since the 1990s. Türkiye has demonstrated significant advancements in its efforts to achieve the Sustainable Development Goals (SDGs), combat poverty, inequality, and environmental degradation, as well as foster economic growth and social inclusion. Considerable effort has been dedicated to formulating and implementing the 2030 Agenda for Sustainable Development, with a primary objective of achieving the Sustainable Development Goals (SDGs). Substantially, most of these goals have been included in legislative and policy frameworks. However, the 2023 Sustainable Development Report highlights that there is still room for improvement in implementation and projects. According to the report, Türkiye is positioned at 72nd place among 166 nations in the Sustainable Development Goals Index, with a corresponding score of 70.8. The report highlights that Türkiye faces significant challenges in 10 out of the 17 goals while encountering substantial barriers in 5. In this respect, this book is dedicated to exploring the various dimensions of Türkiye's achievements within the framework of the Sustainable Development Goals. It offers critical insights, data-driven analyses, and a nuanced understanding of Türkiye's performance, successes, and areas for improvement. We hope this book will serve as a valuable resource for policymakers, scholars, practitioners, and the global community by providing thorough research, critical analysis, and intellectual contributions. The contributors of this book anticipate that the perspectives presented within its pages will stimulate well-informed discussions, encourage the formulation of policies grounded in empirical evidence, and foster collaborative efforts to achieve a more sustainable future for Türkiye and the international community. We would like to extend our sincere appreciation to the authors and referees who have generously shared their expertise and dedicated efforts toward developing this essential scholarly work. Their collective efforts have enriched the discourse on sustainable development and positioned Türkiye on the global stage as a nation committed to realising a better, more equitable, and sustainable world for all.
Keywords: 300